Analisis Gaya Kepemimpinan Dan Komitmen Organisasi Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Intervening - sudaryanto sudaryanto (UPAJIWA, 2020)
The purpose of this research are : (1) To know whether leadership style an effect on work motivation of Bawaslu D.I. Yogyakarta, (2) To know whether organizational commitmen has an effect on motivation employee work of Bawaslu D.I. Yogyakarta,(3) To know whether leadership style and organizational commitmen influence to motivation employee work Bawaslu D.I. Yogyakarta,(4) To know whether leadership style have an effect on to performance employee work of Bawaslu D.I. Yogyakarta,(5) To know whether organizational commitment have an effect on to performance employee work of Bawaslu D.I. Yogyakarta,(6) To know whether leadership style and Organizational Commitment have an effect on to performance employee work to Bawaslu D.I. Yogyakarta,(7) To know whether leadership style, organizaational commitment and motivasion have an effecton to perfomance employee work to Bawaslu D.I. Yogyakarta The variables in this study are leadership style, organizational commitment, motivation and employee performance.Population in this research is employee of Bawaslu D.I. Yogyakarta, which amounts to 31 people. Collection techniques and phat analysis using Smart PLS 3,0. Kewords : Leadership Style, Organizational Commitment, Motivation and Performence